2008
DOI: 10.1016/j.biocontrol.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and seasonal phenology of aboveground arthropods in conventional and transgenic maize crops in Central Spain

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 40 publications
6
39
0
Order By: Relevance
“…Similarly to spiders and harvestmen (Řezáč et al 2006), we could not detect any treatment effect on the assemblage of carabid beetles in any of the study fields. Our results are thus congruent with previous findings (Volkmar & Freier 2003;Candolfi et al 2004;Pons et al 2005;Eizaguirre et al 2006;Farinos et al 2008;Balog et al 2011), including those from the Czech Republic. No significant negative effect of Bt maize on carabid beetles, rove beetles, and spiders was found in the study from south-easten part of the Czech Republic (Habuštová et al 2006) nor significant differences between Bt maize and izogenic cultivar were found in the occurrence of aphids, thrips, and predatory bugs (Sehnal et al 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly to spiders and harvestmen (Řezáč et al 2006), we could not detect any treatment effect on the assemblage of carabid beetles in any of the study fields. Our results are thus congruent with previous findings (Volkmar & Freier 2003;Candolfi et al 2004;Pons et al 2005;Eizaguirre et al 2006;Farinos et al 2008;Balog et al 2011), including those from the Czech Republic. No significant negative effect of Bt maize on carabid beetles, rove beetles, and spiders was found in the study from south-easten part of the Czech Republic (Habuštová et al 2006) nor significant differences between Bt maize and izogenic cultivar were found in the occurrence of aphids, thrips, and predatory bugs (Sehnal et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…In most cases, assemblages of epigeal arthropods seemed not to be affected by presence of transgenic Bt maize (Volkmar & Freier 2003;Candolfi et al 2004;Sehnal et al 2004;Habuštová et al 2005Habuštová et al , 2006Pons et al 2005;Eizaguirre et al 2006;Farinos et al 2008;Balog et al 2011; but see Wold et al 2001), and these results were repeated also for Bt cotton and vegetables (Leslie et al 2007;Torres & Ruberson 2007). Indeed, some authors conclude that compared to conventional farming, the use of transgenic plants enhances arthropod biodiversity in crop fields via reduced input of insecticides to the system (Ferry et al 2006;Leslie et al 2007).…”
mentioning
confidence: 96%
“…Potential impacts of Bt maize on the environment to be considered included those for non-target arthropods (NTAs), an important component of agro-ecosystems formed by non-target herbivores and pests' natural enemies, among other functional groups (Asín & Pons, 1998;Albajes et al, 2003;de la Poza et al, 2005;Farinós et al, 2008;Lumbierres et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In pitfall trapping two families, Carabidae and Staphylinidae, and two orders, Dermaptera and Araneae, were recorded. These predatory groups were selected according to the abundance and potential effects recorded in previous field trials (Lang et al, 1999;Albajes et al, 2003;Jasinski et al, 2003;de la Poza et al, 2005;Farinós et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation